Blockade of GABA transporter-1 and GABA transporter-3 in the lateral habenula improves depressive-like behaviors in a rat model of Parkinson's disease. (15th December 2020) - Lyu, Shuxuan; Guo, Yuan; Zhang, Li; Wang, Yong; Tang, Guoyi; Li, Ruotong; Yang, Jie; Gao, Shasha; Ma, Borui; Liu, Jian
Abstract: The hyperactivity of the lateral habenula (LHb) is closely associated with depression. At present, it is unknown how GABA transporter (GAT) in the LHb affects depressive-like behaviors, particularly in Parkinson's disease (PD)-related depression. In this study, unilateral 6-hydroxydopamine lesions of the substantia nigra pars compacta (SNc) in rats induced depressive-like behaviors and led to hyperactivity of LHb neurons compared to sham-lesioned rats. Intra-LHb injection of GAT-1 inhibitor NO-711 produced antidepressant-like responses, decreased firing rate of LHb neurons, and increased levels of LHb extracellular GABA in sham-lesioned and the lesioned rats. Further, the dose producing behavioral effects in the lesioned rats was lower than that of sham-lesioned rats. In the lesioned rats, the duration of inhibitory effect on the firing rate and increased levels of the GABA induced by NO-711 was longer than those in sham-lesioned rats, respectively. Intra-LHb injection of GAT-3 inhibitor SNAP-5114 improved depressive-like behaviors and decreased firing rate of LHb neurons in the lesioned rats, but not in sham-lesioned rats. SNAP-5114 increased LHb GABA levels in the lesioned rats, whereas did not alter that in sham-lesioned rats. These changes were involved in the down-regulated expression of LHb GAT-1 and GAT-3 after lesioning the SNc. These findings suggest that GAT-1 plays a major role in transporting LHb GABA under physiological conditions, and depletion of dopamine increases the transport capacity of GAT-3 in the LHb. Further, the study provides evidence that GAT-1 and GAT-3 in the LHb are involved in the regulation of PD-related depression. Highlights: Blockade of LHb GAT-1 produced antidepressant-like effects in sham and SNc lesioned rats. Blockade of LHb GAT-3 improved depressive-like behaviors only in lesioned rats. GAT-1 blocker inhibited LHb neurons in both groups and GAT-3 only in lesioned rats. Both GAT-1 and GAT-3 play a role in transporting LHb GABA after SNc lesioning. Lesions of the SNc decreased the expression of GAT-1 and GAT-3 in the LHb.